Preparation method of high-power lead manganese niobate-lead zirconate titanate piezoelectric ceramic material
By optimizing the component structure and preparation process of manganese lead niobate-lead zirconium titanate, the problem of poor performance of existing piezoelectric ceramic materials under high power and high field strength conditions is solved, and the preparation of ceramic materials with high mechanical quality factors and excellent piezoelectric properties is achieved, which is suitable for high-power piezoelectric devices.
Patent Information
- Application Number
- CN202411663912.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-25
AI Technical Summary
Existing piezoelectric ceramic materials are difficult to meet the needs of high mechanical quality factors, low electrical loss and good temperature stability under high power and high field strength conditions.
By optimizing the component structure and preparation process of manganese lead niobate-lead zirconium titanate material, ceramic materials with high mechanical quality factors and excellent piezoelectric properties are prepared using B-position doping formulas, including ball milling, prefiring, glue discharge, sintering and polarization.
The mechanical quality factor of ceramic materials reaches 2000, the piezoelectric performance d33 reaches 310pC/N, the dielectric loss is low, and the temperature stability is good. It is suitable for high-power piezoelectric devices.
Smart Images

Figure CN119874355A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-power piezoelectric ceramics, and in particular to a method for preparing a high-power lead manganese niobate-lead zirconate titanate piezoelectric ceramic material. Background Art
[0002] As a type of electronic material, piezoelectric materials are widely used in the fields of medical treatment, communication, manufacturing and intelligent systems. With the deepening and refinement of application scenarios, conventional P4 and P8 piezoelectric ceramic materials are gradually unable to meet market demand. New high-power piezoelectric ceramic materials need to meet multiple performance requirements: (1) Higher mechanical quality factor Q m and low mechanical loss; (2) can withstand high-power electric fields and have low electrical losses under high field strengths; (3) have good piezoelectric properties and good temperature stability.
[0003] In view of the above requirements, it is urgent to conduct more in-depth research on the component structure and properties of lead manganese niobate-lead zirconate titanate materials. It is of great significance to explore a high-power piezoelectric ceramic material through the design and development of component doping, phase structure and preparation process. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a high-power lead manganese niobate-lead zirconate titanate piezoelectric ceramic material. The piezoelectric ceramic material obtained by the preparation method has a mechanical quality factor of 2000 and a d 33 The piezoelectric performance of ~310pC / N includes the following steps:
[0005] Step S1: Mixing ingredients according to the general formula of a high-power piezoelectric ceramic xPb(Mn 1 / 3 Nb 2 / 3 )O3-(1-x)Pb(Zr y Ti (1-y) O3-zwt% Co2O3, the raw materials are Pb3O4, TiO2, ZrO2, MnO2, Nb2O5, Co2O3, the raw materials are weighed according to the stoichiometric ratio of the general formula, mixed and ball-milled, and dried after ball-milling;
[0006] Step S2: pre-calcining, the powder obtained after drying in S1 is mixed with a small amount of water and dry-pressed into a block, placed in a crucible, and then pre-calcined in a muffle furnace, and the powder is coarsely crushed after pre-calcining;
[0007] Step S3: secondary ball milling, the powder obtained in S2 is subjected to secondary ball milling and drying, then polyethylene solution is added to grind it evenly, and then sieved;
[0008] Step S4: forming, the powder obtained in step S3 is pressed into tablets by a tablet press to form a ceramic embryo;
[0009] Step S5: debinding, placing the embryo body obtained in S4 into a muffle furnace for debinding to obtain a debinded embryo body;
[0010] Step S6: sintering, placing the debinded embryo obtained in S5 into a muffle furnace, covering the embryo with zirconium dioxide powder and sintering to obtain a ceramic sheet;
[0011] Step S7: machining, machining the ceramic obtained in S6 on a grinding and polishing machine, forming it into a designed shape, and cleaning it;
[0012] Step S8: burning the silver electrode, applying the silver electrode on the surface of the ceramic to be polarized in S7, and then placing it in a muffle furnace to burn the silver to obtain a silver-coated ceramic sheet;
[0013] Step S9: Polarization test: The ceramic obtained in S8 is polarized and then cleaned; after cleaning, it is placed for 24 hours before testing.
[0014] In one embodiment of the present invention, the high power lead manganese niobate-lead zirconate titanate piezoelectric ceramic is of the general formula xPb(Mn 1 / 3 Nb 2 / 3 )]O3-(1-x)Pb(Zr y Ti (1-y) ]O3-zmol%Co2O3 represents the composition of the material, where x=0.04~0.10; y=0.45~0.55; z=0~0.02.
[0015] In one embodiment of the present invention, the initial ball milling time in step S1 is 12 hours.
[0016] In one embodiment of the present invention, in step S2, the pre-calcination heating rate is 3°C / min to 10°C / min, the pre-calcination temperature is 850°C, and the pre-calcination holding time is 2 hours to obtain a pre-calcined powder.
[0017] In one embodiment of the present invention, the amount of polyvinyl alcohol added in step S3 is 7wt% to 10wt%, the secondary ball milling time is 24 hours, and the sieve is 100 to 200 meshes.
[0018] In one embodiment of the present invention, the binder removal temperature in step S5 is 600° C., and the binder removal insulation time is 2 hours.
[0019] In one embodiment of the present invention, the sintering temperature rise and fall system in step S6 is as follows: heating to 1000-1100°C at a heating rate of 2°C / min-10°C / min, keeping warm for 1 hour, then heating to 1100-1300°C at a heating rate of 1.5°C / min-3°C / min, keeping warm for 2-3 hours, and after the insulation, cooling to 800°C at a cooling rate of 3°C / min-10°C / min, and then naturally cooling to room temperature.
[0020] In one embodiment of the present invention, the silver burning step in step S8 is: heating to 650-850° C. at a rate of 3° C. / min-10° C. / min, and keeping at this temperature for 20 min-40 min.
[0021] In one embodiment of the present invention, the polarization process in step S9 is performed at an electric field strength of 3 kv / mm to 4 kv / mm and a polarization time of 10 min to 30 min.
[0022] The above technical solution of the present invention has the following advantages over the prior art: the piezoelectric ceramic material preparation method of the present invention, the lead manganese niobate-lead zirconate titanate piezoelectric ceramic material prepared by optimizing the B-site doping formula, has a mechanical quality factor of 2000 and a d 33 The piezoelectric performance is 310pC / N, the dielectric loss is 0.3%, and the mechanical quality factor is 1500. 33 The piezoelectric performance of the ceramic is 350pC / N, and the dielectric loss of the ceramic is 0.45%. Compared with the conventional P8 piezoelectric ceramic mechanical quality factor of 1200, the piezoelectric performance d 33 ~220pC / N have been greatly improved;
[0023] At the same time, the present invention includes pure PMnN-PZT and a trace amount of Co2O3 doped PMnN-PZT piezoelectric ceramics. Through structural adjustment, the ceramic component is a tetragonal phase piezoelectric ceramic material close to the quasi-morphic phase boundary, which can maintain the stability of the phase structure during the temperature rise and fall process, and thus has high temperature stability. In addition, the ceramic component has high process stability, is suitable for mass production, and is expected to be applied to high-power piezoelectric devices such as ultrasonic motors and ultrasonic transducers. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to make the contents of the present invention more clearly understood, the present invention is further described in detail below based on specific embodiments of the present invention in conjunction with the accompanying drawings.
[0025] Figure 1 It is a dielectric temperature spectrum prepared by the method for preparing high-power lead manganese niobate-lead zirconate titanate piezoelectric ceramic material of the present invention;
[0026] Figure 2It is a PE curve diagram of the piezoelectric ceramic material prepared by the method for preparing the piezoelectric ceramic material of the present invention. DETAILED DESCRIPTION
[0027] The present invention prepares a high-power lead manganese niobate-lead zirconate titanate piezoelectric ceramic material. By fine-tuning the components and changing the preparation process, a tetragonal piezoelectric ceramic with good temperature stability can be obtained. The ceramic material has high piezoelectric performance and high mechanical quality factor, which is conducive to the application in high-power piezoelectric devices.
[0028] The present invention is further described in detail below in conjunction with specific implementation cases.
[0029] Embodiment 1
[0030] The chemical formula of a high-power lead manganese niobate-lead zirconate titanate piezoelectric ceramic material in this embodiment is xPb(Mn 1 / 3Nb 2 / 3 )O3-(1-x)Pb(Zr 0.5 Ti 0.5 )O3, where x=0.6, 0.7, 0.8.
[0031] S1: Pb3O4, TiO2, ZrO2, MnO2, Nb2O5 and Co2O3 are weighed and prepared as raw materials. All raw materials are commercially available industrial raw materials. They are then ball-milled and dried. The ball-milling medium is deionized water. The raw materials are dried after ball-milling for 12 hours.
[0032] S2: The dried powder is mixed with a small amount of water and dry-pressed into a block, which is placed in a crucible and then pre-calcined in a muffle furnace. The pre-calcination heating rate is 3°C / min, the pre-calcination temperature is 800°C, and the pre-calcination insulation time is 2 hours. After pre-calcination, the powder is coarsely crushed to obtain pre-calcined powder.
[0033] S3: Secondary ball milling: the powder obtained in S2 is subjected to secondary ball milling and drying for 24 hours, and then dried. After drying, polyethylene solution is added and ground evenly, the amount of polyvinyl alcohol is 8wt%, and sieved, the sieve is 100 mesh.
[0034] S4: molding, the powder obtained in step S3 is pressed into tablets by a tablet press to form a ceramic body.
[0035] S5 debinding, placing the embryo body obtained in S4 into a muffle furnace for debinding, the debinding temperature is 600° C., the debinding heat preservation time is 2 hours, and then the debinded embryo body is obtained.
[0036] S6: sintering. The debinded embryo obtained in S5 is placed in a muffle furnace, and the embryo is covered with zirconium dioxide powder for burial firing. The sintering temperature rise and fall system is as follows: the temperature is increased to 1000°C at a rate of 3°C / min, kept warm for 1 hour, then increased to 1160°C at a rate of 2°C / min, kept warm for 3 hours, and after the end of the holding period, the temperature is reduced to 800°C at a rate of 4°C / min, and then naturally cooled to room temperature to obtain a ceramic sheet.
[0037] S7: machining, machining the ceramic obtained in S6 on a grinding and polishing machine, forming it into a designed shape, and cleaning it.
[0038] S8: Silver electrode burning: apply silver electrode on the surface of the ceramic to be polarized in S7, and then place it in a muffle furnace to burn silver. The silver burning steps are: heating up to 800°C at a rate of 3°C / min, and keeping at this temperature for 30 minutes. A silver-coated ceramic sheet is obtained.
[0039] S9: Polarization test: The ceramic obtained in S8 is polarized with silicone oil, with a polarization voltage of 4 kv / mm, a polarization temperature of 120°C, and a polarization time of 20 min. After polarization, it is cleaned to obtain a high-power lead manganese niobate-lead zirconate titanate piezoelectric ceramic material. The ceramic is then tested after being placed for 24 hours. The electrical performance test results of implementation case 1 are shown in Table 1, and the dielectric temperature spectrum is shown in Table 1. Figure 1 ,PE curve see Figure 2 .
[0040] Embodiment 2
[0041] The chemical formula of a high-power lead manganese niobate-lead zirconate titanate piezoelectric ceramic material in this embodiment is 0.08Pb(Mn 1 / 3 Nb 2 / 3 )O3-0.92Pb(Zr 0.5 Ti 0.5 )O3-zmol%Co2O3, where z=0.5, 1, 1.5.
[0042] Pb3O4, TiO2, ZrO2, MnO2, Nb2O5, and Co2O3 are used as raw materials and prepared according to the general chemical formula. The high-power lead manganese niobate-lead zirconate titanate piezoelectric ceramics are obtained by the preparation method of implementation and case 1. The difference from case 1 is that the pre-sintering temperature is 850°C, and the temperature is increased to 1100°C at a heating rate of 3°C / min during the sintering process, and then heated to 1240°C at a heating rate of 2°C / min, and heated for 2 hours. After the end of the insulation, the temperature is reduced to 800°C at a cooling rate of 4°C / min, and then naturally cooled to room temperature to obtain a ceramic sheet. The other process steps and parameters are the same as those of implementation case 1. The electrical performance test results of implementation case 2 are shown in Table 2.
[0043] Table 1: Piezoelectric performance test and dielectric properties of Example 1
[0044] Components <![CDATA[d 33 (pC / N)]]> tanδ <![CDATA[k p ]]> <![CDATA[Q m ]]> <![CDATA[T c (℃)]]> x=0.06 300 0.29% 0.56 1730 351 x=0.07 310 0.32% 0.57 2011 344 x=0.08 320 0.45% 0.59 1708 343 P8 220 0.3% 0.53 1200 300
[0045] Table 2: Piezoelectric performance test and dielectric properties of Example 2
[0046] Components <![CDATA[d 33 (pC / N)]]> tanδ <![CDATA[k p ]]> <![CDATA[Q m ]]> <![CDATA[T c (℃)]]> z=0.5 330 0.45% 0.60 1230 343 z=1 380 0.40% 0.62 1560 342 z=1.5 370 0.43% 0.60 1420 341
[0047] In this embodiment 1, compared with the P8 series piezoelectric ceramics, the performance of the component x=0.8 is significantly improved, d 33 In the second implementation, compared with the P8 series piezoelectric ceramics, the performance of component Z=1 is significantly improved, d 33 Improved by 72%, Q m Improved by 28%. Through doping modification, the performance of piezoelectric ceramics has been optimized. At the same time, the Curie temperature of piezoelectric ceramics has also increased by 40°C, expanding the temperature range of hard piezoelectric ceramics.
[0048] In summary, the ceramic material of the x=0.07 system in Example 1 has a relatively high mechanical quality factor Q m ~2000, which is 67% higher than that of P8 material, and has a better piezoelectric coefficient d 33 ~310pC / N. In addition, the ceramics of the component z=1 series in the second embodiment have a relatively high piezoelectric coefficient d 33 ~380pC / N is 72% higher than P8 material, and has better Q m ~ 1500. In summary, the new piezoelectric ceramic materials in this system have greater performance parameters than the currently commercially available conventional piezoelectric ceramic materials and are suitable for use in high-power piezoelectric devices such as ultrasonic motors, piezoelectric transformers, and ultrasonic transducers.
[0049] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a high-power lead manganese niobate-lead zirconate titanate piezoelectric ceramic material, wherein the piezoelectric ceramic material obtained by the preparation method has a mechanical quality factor of 2000 and a d 33 The piezoelectric performance of ~310pC / N is characterized by: The steps include: Step S1: Mixing ingredients according to the general formula of a high-power piezoelectric ceramic xPb(Mn 1 / 3 Nb 2 / 3 )O3-(1-x)Pb(Zr y Ti (1-y) O3-zwt% Co2O3, the raw materials are Pb3O4, TiO2, ZrO2, MnO2, Nb2O5, Co2O3, the raw materials are weighed according to the stoichiometric ratio of the general formula, mixed and ball-milled, and dried after ball-milling; Step S2: pre-calcining, the powder obtained after drying in S1 is mixed with a small amount of water, dry-pressed into a block, placed in a crucible, and then pre-calcined in a muffle furnace, and the powder is coarsely crushed after pre-calcining; Step S3: secondary ball milling, the powder obtained in S2 is subjected to secondary ball milling and drying, then polyethylene solution is added to grind it evenly, and then sieved; Step S4: forming, the powder obtained in step S3 is pressed into tablets by a tablet press to form a ceramic embryo; Step S5: debinding, placing the embryo body obtained in S4 into a muffle furnace for debinding to obtain a debinded embryo body; Step S6: sintering, placing the debinded embryo obtained in S5 into a muffle furnace, covering the embryo with zirconium dioxide powder and sintering to obtain a ceramic sheet; Step S7: machining, machining the ceramic obtained in S6 on a grinding and polishing machine, forming it into a designed shape, and cleaning it; Step S8: burning the silver electrode, applying the silver electrode on the surface of the ceramic to be polarized in S7, and then placing it in a muffle furnace to burn the silver to obtain a silver-coated ceramic sheet; Step S9: Polarization test: The ceramic obtained in S8 is polarized and then cleaned; after cleaning, it is placed for 24 hours before testing.
2. The method for preparing a piezoelectric ceramic material according to claim 1, characterized in that: Among them, high-power manganese lead niobate-lead zirconate titanate piezoelectric ceramics are generally formulated as xPb(Mn 1 / 3 Nb 2 / 3 )]O3-(1-x)Pb(Zr y Ti (1-y) ]O3-zmol%Co2O3 represents the composition of the material, where x=0.04~0.10; y=0.45~0.55; z=0~0.
02.
3. The method for preparing a piezoelectric ceramic material according to claim 1, characterized in that: The initial ball milling time in step S1 is 12 hours.
4. The method for preparing a piezoelectric ceramic material according to claim 1, characterized in that: In step S2, the pre-calcination heating rate is 3°C / min to 10°C / min, the pre-calcination temperature is 850°C, and the pre-calcination heat preservation time is 2 hours to obtain a pre-calcined powder.
5. The method for preparing a piezoelectric ceramic material according to claim 1, characterized in that: The amount of polyvinyl alcohol added in step S3 is 7wt% to 10wt%, the secondary ball milling time is 24 hours, and the sieve is 100 to 200 meshes.
6. The method for preparing a piezoelectric ceramic material according to claim 1, characterized in that: In step S5, the debinding temperature is 600° C. and the debinding holding time is 2 hours.
7. The method for preparing a piezoelectric ceramic material according to claim 1, characterized in that: The sintering temperature rise and fall system in step S6 is as follows: increase the temperature to 1000-1100°C at a heating rate of 2°C / min-10°C / min, keep it warm for 1 hour, then increase the temperature to 1100-1300°C at a heating rate of 1.5°C / min-3°C / min, keep it warm for 2-3 hours, and after the insulation, reduce the temperature to 800°C at a cooling rate of 3°C / min-10°C / min, and then naturally cool to room temperature.
8. The method for preparing a piezoelectric ceramic material according to claim 1, characterized in that: The silver burning step in step S8 is: heating to 650-850° C. at a rate of 3° C. / min-10° C. / min, and keeping at this temperature for 20 min-40 min.
9. The method for preparing a piezoelectric ceramic material according to claim 1, characterized in that: In step S9, the polarization process is performed at an electric field strength of 3 kv / mm to 4 kv / mm and a polarization time of 10 min to 30 min.
Citation Information
Cited By
Preparation method of samarium trioxide doped lead niobate and lead zirconate titanate piezoelectric fiber sensor
CN120649162A
Preparation method of tin dioxide doped lead niobate and lead zirconate titanate piezoelectric fiber sensor
CN120649163A